CPSF6-RARγ interacts with histone deacetylase 3 to promote myeloid transformation in RARG-fusion acute myeloid leukemia - Tianhui Liu; Tanzhen Wang; Lijuan Qi; Yujie Liu; Meng Shan; Fuqiang Wang; Yanglan Fang; Sining Liu; Lijun Wen; Suning Chen; Depei Wu; Yang Xu (Nature Communications)
Abstract Acute myeloid leukemia (AML) with retinoic acid receptor gamma (RARG) fusions, which exhibits clinical features resembling acute promyelocytic leukemia (APL), has been identified as a new subtype with poor clinical outcomes. The underlying mechanism of RARG-fusion leukemia remains poorly understood, and needs to be explored urgently to instruct developing effective therapeutic strategies. Here, using the most prevalent RARG fusion, CPSF6-RARG (CR), as a representative, we reveal that the CR fusion, enhances the expansion of myeloid progenitors, impairs their maturation and synergizes with RAS mutations to drive more aggressive myeloid malignancies. Mechanistically, CR fusion interacts with histone deacetylase 3 (HDAC3) to suppress expression of genes associated with myeloid differentiation including the myeloid transcription factor PU.1. Disrupting CR-HDAC3 interaction, restores PU.1 expression and myeloid differentiation. Furthermore, HDAC inhibitors effectively suppress CR-driven leukemia in vitro and in vivo. Hence, our data reveals the molecular bases of oncogenic CR fusion and provides a potential therapeutic approach against AML with CR fusion.